Preparation method and application of self-supporting copper selenide nanosheet electrocatalyst
By growing copper hydroxide nanoribbons on foam copper and reacting with sodium hydrogen selenide to form a self-supported copper selenide nanosheet electrocatalyst, the problem of low proton and electron transfer efficiency in eCO2RR is solved, and efficient carbon dioxide reduction and carbon monoxide are achieved The current density is reduced and the cost is reduced.
Patent Information
- Application Number
- CN202310057698.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-01-18
AI Technical Summary
Electrocatalytic carbon dioxide reduction reaction (eCO2RR) faces the challenge of reducing CO2 activation energy and proton and electron transfer processes, resulting in low conversion efficiency and polymeric binders of powder catalysts slow down electron transfer, hindering reaction kinetics.
The preparation method of self-supported copper selenide nanosheet electrocatalyst is adopted to grow copper hydroxide nanobelts on foam copper through metal peeling and hydrothermal reaction, and then react with sodium hydrogen selenide precursor to form copper selenide nanosheets, combining three-dimensional Metal skeleton forms a multi-dimensional composite structure.
It achieves efficient carbon dioxide reduction under neutral conditions, with the Faraday efficiency reaching 85.6%, the carbon monoxide partial current density is as high as 12.0mA cm-2, the H2/CO ratio is adjustable, and the conversion frequency TOF reaches 1303h-1, which is much higher than that of copper-based catalysts. , and reduces the cost of use.
Smart Images

Figure CN116043258B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of an electrocatalyst, and in particular to a preparation method and application of a self-supporting copper selenide nanosheet electrocatalyst. Background Art
[0002] Electrocatalytic carbon dioxide reduction reaction (eCO 2 RR) is an effective CO 2 Conversion methods that convert atmospheric carbon dioxide into valuable fuels and chemicals such as carbon monoxide, formate, hydrocarbons and alcohols through renewable energy and surplus nuclear power, while achieving electrical energy storage and closing the carbon cycle.
[0003] eCO 2 RR faces the challenge of reducing CO 2 The activation energy barrier and the challenges of further proton and electron transfer processes, especially due to the multiple proton and electron transfer processes, the generation of multi-carbon products is slow and inevitably competes with the hydrogen evolution reaction (HER), resulting in low conversion efficiency in practical applications.
[0004] Therefore, it is of great significance to develop and utilize efficient catalysts to regulate the proton / electron transfer process to obtain the desired target product. However, polymer binders used in powder catalysts slow down the electron transfer and hinder the reaction kinetics. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a self-supporting copper selenide nanosheet electrocatalyst with excellent electrochemical performance;
[0006] The second object of the present invention is to provide the use of the self-supporting copper selenide nanosheet electrocatalyst prepared by the above method as a cathode catalyst for electrocatalytic carbon dioxide reduction under neutral conditions.
[0007] Technical solution: The method for preparing the self-supporting copper selenide nanosheet electrocatalyst of the present invention comprises the following steps:
[0008] (1) immersing the copper foam in a mixed solution of alkali and persulfate, so that metal stripping and oxidation reactions occur in the solution to obtain self-supporting copper hydroxide nanobelts;
[0009] (2) mixing and dissolving selenium powder and sodium borohydride powder to obtain a sodium hydrogen selenide precursor;
[0010] (3) The self-supporting copper hydroxide nanobelts are mixed with a sodium hydride selenide precursor and subjected to a hydrothermal reaction, and the obtained product is the self-supporting copper selenide nanosheet electrocatalyst.
[0011] Wherein, in step (1), the molar ratio of the alkali to the persulfate is 19:1-20:1, and more preferably 20:1.
[0012] Wherein, in step (1), the thickness of the copper foam is 9-11 mm, and more preferably 10 mm.
[0013] Wherein, in step (2), the molar ratio of the selenium powder to sodium borohydride is 4:1-5:1; more preferably 5:1.
[0014] Wherein, in step (3), the temperature of the hydrothermal reaction is 175-185°C and the time is 12-14h.
[0015] Wherein, in step (1), the foamed copper is pretreated with dilute hydrochloric acid and water.
[0016] Wherein, in steps (1) and (2), the solvent used for dissolution is water.
[0017] Among them, the copper selenide assembled fibers have planar nanosheet arrays on each nanowire in the three-dimensional metal skeleton.
[0018] The self-supporting copper selenide nanosheet electrocatalyst prepared by the above method is used as a cathode catalyst for electrocatalytic carbon dioxide reduction under neutral conditions.
[0019] The self-supporting copper selenide nanosheet electrocatalyst prepared above is used to convert carbon dioxide, which specifically includes the following steps:
[0020] (1) adding the copper selenide electrocatalyst into a mixed solution containing ethanol and a binder and subjecting it to ultrasonic treatment to obtain a catalyst ink-like liquid;
[0021] (2) slowly dripping the ink-like liquid onto the treated conductive carbon paper, and drying at room temperature to form a working electrode;
[0022] (3) Electrochemical experiments were conducted using a three-electrode system in an H-type electrolytic cell. KHCO 3 Electrolyte;
[0023] (4) Polarize under different constant potential polarization test conditions, take a certain volume of gas from the H-type electrolyzer at regular intervals and inject it into a gas chromatograph for testing; combine the data obtained from the gas chromatograph with the electrochemical data to analyze the electrochemical properties of the catalyst material.
[0024] Wherein, in step (1), the self-supporting copper selenide nanosheet electrocatalyst is 6.5-7.5 mg; the volumes of ethanol and binder are 950 μL and 50 μL respectively.
[0025] Wherein, in step (2), the treated conductive carbon paper is processed by cutting the conductive carbon paper; preferably, the cutting size is 1 x 1.5 cm 2 , and stick an insulating tape on one side to ensure that only a partial area of the loading area is left for dripping the catalyst ink-like liquid; preferably, only a loading area of 1 x 1 cm is left 2 One side is provided to facilitate the addition of catalyst ink-like liquid.
[0026] Wherein, in step (3), the KHCO 3 The concentration of the electrolyte is 0.4-0.5 mol / L.
[0027] Principle of the invention: The present invention prepares copper hydroxide nanobelts grown on copper foam by a metal stripping scheme, and then obtains a self-supporting copper selenide nanosheet electrocatalyst using sodium hydride selenide by a hydrothermal method. The present invention in situ assembles copper selenide 2D nanosheets on a copper foam metal substrate with a 3D foam skeleton to obtain a multi-dimensional composite structure self-supporting copper selenide electrocatalyst.
[0028] Beneficial effects: Compared with the prior art, the present invention has achieved the following significant effects: (1) The catalyst exhibits excellent electrochemical performance. At a voltage of -1.2 V vs. RHE, the Faraday efficiency of electrocatalytic carbon dioxide to carbon monoxide conversion is as high as 85.6%, and the carbon monoxide partial current density is as high as 12.0 mA cm -2 , H is achieved at a wider potential 2 / CO ratio, i.e. 0.8 to 6.0, achieved an excellent conversion frequency TOF of 1303h -1 , which can achieve a high Faraday efficiency and a high carbon monoxide partial current density that are much higher than those of copper-based catalysts. (2) The catalyst can reduce the cost of use while ensuring high catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The Cu(OH) prepared in Examples 1, 2 and 3 of the present invention 2 -Scanning electron microscope image of CF;
[0030] Figure 2 The Cu prepared in Example 2 of the present invention 3 Se 2 -Scanning electron microscope image of CF;
[0031] Figure 3 The Cu prepared in Example 2 of the present invention 3 Se 2 - Transmission electron microscopy image of CF;
[0032] Figure 4 The Cu prepared in Example 2 of the present invention3 Se 2 - High-resolution transmission and selected area electron diffraction images of CF;
[0033] Figure 5 The Cu prepared in Example 2 of the present invention 3 Se 2 - High-angle annular dark-field scanning transmission electron microscopy of CF and elemental distribution images of copper and selenium;
[0034] Figure 6 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -X-ray diffraction pattern of CF-2;
[0035] Figure 7 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -X-ray photoelectron spectroscopy analysis of CF-2;
[0036] Figure 8 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -Scanning cyclic voltammetry curve of CF-2;
[0037] Fig. 9 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -Linear sweep voltammetry curve of CF-2;
[0038] Fig.10 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se2 -CF and Cu prepared in Example 3 3 Se 2 - Total Faradaic efficiency diagram of carbon monoxide and hydrogen products of CF-2;
[0039] Fig.11 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 - Current distribution diagram of carbon monoxide, the product of CF-2;
[0040] Fig.12 They are respectively the Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -Electrochemical specific surface area test of CF-2;
[0041] Fig.13 They are respectively the Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -CF-2 conversion coefficient diagram;
[0042] Fig.14 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -Tafel curve of CF-2;
[0043] Fig.15 The Cu prepared in Example 1 of the present invention 3 Se 2 -CF-1, Cu prepared in Example 2 3 Se 2 -CF and Cu prepared in Example 3 3 Se 2 -CF-2H 2 / CO molar ratio;
[0044] Fig.16 The Cu prepared in Example 2 3 Se 2 -CF H 2 / CO molar ratio;
[0045] Fig.17 The Cu prepared in Example 2 of the present invention 3 Se 2 -CF was subjected to constant potential polarization test at -1.0 V for 12 h. DETAILED DESCRIPTION
[0046] The present invention is described in further detail below.
[0047] Example 1
[0048] (1)Cu(OH) 2 Preparation of -CF
[0049] 0.2 mol NaOH and 0.01 mol (NH 4 ) 2 S 2 O 8 The powder was dissolved in 100 mL of deionized water and stirred for 10 min to form a uniform solution. A piece of copper foam pretreated with dilute hydrochloric acid and deionized water was immersed in the above solution. In the presence of hydroxide ions, metal stripping and oxidation reactions occurred to obtain a self-supporting copper hydroxide nanobelt with uniform morphology. After that, it was washed with deionized water and ethanol respectively, and the obtained product was vacuum dried at 60 ° C for 24 h. After vacuum drying, the sample was collected to obtain Cu(OH) 2 -CF. The self-supporting Cu(OH) 2 -CF morphology Figure 1 As shown, it can be seen that Cu(OH) 2 The average diameter of the nanowires is about 200 nm and the length is 2 μm.
[0050] (2) Self-supporting Cu 3 Se 2 Preparation of -CF-1
[0051] 13.7 mg of selenium powder and the corresponding amount of sodium borohydride powder were dispersed in deionized water and stirred for 10 minutes to obtain a sodium hydrogen selenide precursor. The prepared self-supporting copper hydroxide nanobelts were transferred to a stainless steel autoclave lined with sodium hydrogen selenide and subjected to a hydrothermal reaction at 180°C for 12 hours. Afterwards, they were washed with deionized water and ethanol respectively, and the obtained product was vacuum dried at 60°C for 24 hours. After vacuum drying was completed, the sample was collected to obtain a self-supporting Cu 3 Se2 Nanosheet Cu 3 Se 2 -CF-1.
[0052] (3) Preparation of CO2 reduction electrode materials and electrocatalytic CO2 reduction performance testing
[0053] The Cu obtained in (2) 3 Se 2 -CF-1 was used as the working electrode, and a three-electrode system was used to measure its electrocatalytic performance for carbon dioxide reduction on an electrochemical workstation. The scanning cyclic voltammetry curve CV, linear scanning voltammetry curve LSV, Faraday efficiency FE diagram of the product, and partial current j of the product carbon monoxide of the catalytic material were CO Figure, electrochemical specific surface area ECSA test, conversion coefficient TOF diagram, Tafel curve diagram, H 2 :CO molar ratio test chart, please refer to Figure 8 , Fig. 9 , Fig.10 , Fig.11 , Fig.12 , Fig.13 , Fig.14 and Fig.15 ;in Figure 8 The test conditions are: scan rate 50mV / s, voltage range -0.1~-1.5V (vs.RHE), electrolyte solution 0.5M KHCO 3 ; Fig. 9 The test conditions are: scan rate 5mV / s, voltage range -0.1~-1.5V (vs.RHE), electrolyte solution 0.5M KHCO 3 .
[0054] Example 2
[0055] (1)Cu(OH) 2 Preparation of -CF
[0056] 0.2 mol NaOH and 0.01 mol (NH 4 ) 2 S 2 O 8 The powder was dissolved in 100 mL of deionized water and stirred for 10 min to form a uniform solution. A piece of copper foam pretreated with dilute hydrochloric acid and deionized water was immersed in the above solution. Metal stripping and oxidation occurred in the presence of hydroxide ions to obtain a self-supporting copper hydroxide nanobelt with uniform morphology. After that, it was washed with deionized water and ethanol respectively, and the obtained product was vacuum dried at 60 ° C for 24 h. After vacuum drying, the sample was collected to obtain Cu(OH) 2 -CF. The self-supporting Cu(OH)2 -CF morphology see Figure 1 .
[0057] (2) Self-supporting Cu 3 Se 2 Preparation of -CF-2
[0058] 7 mg of selenium powder and the corresponding amount of sodium borohydride powder were dispersed in deionized water and stirred for 10 min to obtain a sodium hydrogen selenide precursor. The prepared self-supporting copper hydroxide nanobelts were transferred to a stainless steel autoclave lined with sodium hydrogen selenide and subjected to a hydrothermal reaction at 180 ° C for 12 h. Afterwards, they were washed with deionized water and ethanol respectively, and the obtained product was vacuum dried at 60 ° C for 24 h. After vacuum drying was completed, the sample was collected to obtain a self-supporting Cu 3 Se 2 Nanosheet Cu 3 Se 2 -CF. The free-standing Cu 3 Se 2 -CF catalyst morphology, please refer to Figure 2 , 3, 4 and 5. Please refer to the XRD for their phase structure characterization Figure 6 , please refer to XPS for element valence information Figure 7 .
[0059] Figure 2 , 3 shows that the fibers surrounded by nanosheets have internal pore structures. Figure 4 In the high-resolution transmission and selected area electron diffraction images of Cu 3 Se 2 The crystal structure of red copper selenite is shown. The interplanar spacing is and The lattice fringes correspond to Cu 3 Se 2 The (220) and (101) faces of Figure 5 As shown, the high-angle annular dark-field scanning transmission electron microscopy image and the corresponding element distribution image show that Se and Cu are in Cu 3 Se 2 Uniform distribution in the nanosheets.
[0060] The phase structure was characterized by X-ray diffraction, such as Figure 6 As shown in Figure 1, the peaks at 43.57°, 50.70°, and 74.35° correspond to the copper foam. Secondly, Cu(OH) 2 The characteristic peak of -CF corresponds well to Cu(OH) 2 phase (PDF#72-0140), confirming that Cu(OH) 2 Then Cu 3 Se2 The characteristic peaks of -CF correspond well to Cu 3 Se 2 phase (PDF#71-0045), confirming that Cu 3 Se 2 The successful synthesis of Cu 3 Se 2 The nanosheets grow along the (220) direction. In addition, there is no Cu(OH) 2 The peak indicates Cu(OH) 2 Completely converted to Cu 3 Se 2 In order to better study the regulation of Cu peripheral electronic structure and Cu-Se bond by different Cu / Se feed ratios, the electronic properties of this series of materials were analyzed by X-ray photoelectron spectroscopy (XPS). Figure 7 As shown in a, the peak of Cu 2p slightly shifts to lower binding energy with decreasing Cu / Se ratio, which indicates the increase of charge density around cationic Cu and the increase of Cu(OH) 2 Cu 2+ Cu + In addition, Figure 7 As shown in Figure b, the peak of Se 3d slightly shifts to a higher binding energy, which is consistent with the results of Cu 2p spectrum analysis. At the same time, with the introduction of anionic Se, there is a continuous electron transfer from Se to Cu. Figure 7 As shown in c, Cu + The normalized peak intensity of Cu 2+ Strong, indicating Cu 2+ The content of Cu is decreasing, and the corresponding + The content is increasing.
[0061] (3) Preparation of CO2 reduction electrode materials and electrocatalytic CO2 reduction performance testing
[0062] The Cu obtained in (2) 3 Se 2 -CF-2 was used as the working electrode and a three-electrode system was used to measure the electrocatalytic performance of carbon dioxide reduction on an electrochemical workstation. The scanning cyclic voltammetry curve, linear scanning voltammetry curve, Faraday efficiency diagram of the product, current distribution diagram of the product carbon monoxide, electrochemical specific surface area test, conversion coefficient diagram, Tafel curve diagram, H 2 ∶CO molar ratio test chart, and Cu 3 Se 2 -CF H 2 For the bar graph of ∶CO molar ratio and constant potential polarization IT stability test, please refer to Figure 8 , Fig. 9 , Fig.10 , Fig.11 , Fig.12 , Fig.13 , Fig.14 , Fig.15 , Fig.16 and Fig.17 .
[0063] Example 3
[0064] (1)Cu(OH) 2 Preparation of -CF
[0065] 0.2 mol NaOH and 0.01 mol (NH 4 ) 2 S 2 O 8 The powder was dissolved in 100 mL of deionized water and stirred for 10 min to form a uniform solution. A piece of copper foam pretreated with dilute hydrochloric acid and deionized water was immersed in the above solution. Metal stripping and oxidation occurred in the presence of hydroxide ions to obtain a self-supporting copper hydroxide nanobelt with uniform morphology. After that, it was washed with deionized water and ethanol respectively, and the obtained product was vacuum dried at 60 ° C for 24 h. After vacuum drying, the sample was collected to obtain Cu(OH) 2 -CF. The self-supporting Cu(OH) 2 -CF morphology see Figure 1 .
[0066] (2) Self-supporting Cu 3 Se 2 Preparation of -CF-3
[0067] 2 mg of selenium powder and the corresponding amount of sodium borohydride powder were dispersed in deionized water and stirred for 10 min to obtain a sodium hydrogen selenide precursor. The prepared self-supporting copper hydroxide nanobelts were transferred to a stainless steel autoclave lined with sodium hydrogen selenide and subjected to a hydrothermal reaction at 180 ° C for 12 h. Afterwards, they were washed with deionized water and ethanol respectively, and the obtained product was vacuum dried at 60 ° C for 24 h. After vacuum drying was completed, the sample was collected to obtain a self-supporting Cu 3 Se 2 Nanosheet Cu 3 Se 2 -CF-3.
[0068] (3) Preparation of CO2 reduction electrode materials and electrocatalytic CO2 reduction performance testing
[0069] The Cu obtained in (2) 3 Se 2-CF-3 was used as the working electrode and a three-electrode system was used to measure the electrocatalytic performance of carbon dioxide reduction on an electrochemical workstation. The scanning cyclic voltammetry curve, linear scanning voltammetry curve, Faraday efficiency diagram of the product, current distribution diagram of the product carbon monoxide, electrochemical specific surface area test, conversion coefficient diagram, Tafel curve diagram, H 2 :CO molar ratio test chart, please refer to Figure 8 , Fig. 9 , Fig.10 , Fig.11 , Fig.12 , Fig.13 , Fig.14 and Fig.15 .
[0070] Cu 3 Se 2 Inspired by the hierarchical structure of nanosheet arrays and the modified electronic structure of Cu sites, the present invention evaluates their electrochemical activity and subsequent selenization to their eCO 2 Impact of RR performance.
[0071] like Figure 8 CV and Fig. 9 As shown in the LSV curves, at each potential, almost all catalysts 2 Saturated 0.5M KHCO 3 The current density in the electrolyte is greater than N 2 Saturated 0.5M KHCO 3 The current density in the electrolyte indicates that they can first conduct CO 2 reduction.
[0072] Cu 3 Se 2 The onset potential of -CF is -229 mV, which is lower than that of Cu 3 Se 2 -CF-1(-267mV),Cu 3 Se 2 -CF-2 (-255mV) and copper foam (-378mV), indicating that the Cu / Se ratio of Cu is 1:0.5 3 Se 2 -CF is more favorable to CO 2 Combination of Figure 2 a As shown in the illustration. Specifically, Cu 3 Se 2 -CF current density reaches -22.91mAcm at -1.0V -2 , which is much higher than other samples, such as Fig.10 Therefore, Cu with a Cu / Se ratio of 1:0.5 3 Se2 -CF presents the largest current density, which is consistent with HER and CO 2 RRs all correspond.
[0073] To further study the CO 2 RR performance, the reduction products were measured by GC instrumentation, where only CO and H were detected 2 , the total Faradaic efficiency is close to 1, indicating that no other products are generated, such as Fig.10 As shown. 3 Se 2 -CF has a higher Faradaic efficiency for CO than other samples. 3 Se 2 The total current of -CF was higher than that of other samples at potentials from -0.6 V to -1.5 V. The CO(j CO ) of the partial current density, such as Fig.11 As shown, Cu 3 Se 2 -CF's j CO Significantly higher than Cu 3 Se 2 -CF-1, Cu 3 Se 2 -CF-2 and Cu foam. Specifically, Cu 3 Se 2 -CF at a potential of -1.2 V CO 11.9 mA cm -2 , more than 2 times higher than other samples.
[0074] To explain the enhanced performance of electrocatalytic CO2 reduction, e.g. Fig.12 As shown, the double layer capacitance C is calculated by using the electrochemically active surface area dl After analysis, it was found that the C dl 2.08mF cm -2 , and Cu 3 Se 2 -CF's C dl The value is 3.19mF cm -2 , C of copper foam dl The value is 2.08mF cm -2 Therefore, Cu 3 Se 2 -CF's C dl The value is about 1.6 times that of copper foam, indicating that its surface area is larger.
[0075] The TOF analysis of Cu 3 Se 2 About eCO 2 Intrinsic activity of RR. Cu3 Se 2 -CF showed a higher TOF of 1303 h at -1.0 V for CO production -1 , is Cu 3 Se 2 -CF-1 and Cu 3 Se 2 -2.38 and 2.24 times of CF-2, such as Fig.13 The Tafel slope analysis was performed on the LSV curves of various samples, among which Cu 3 Se 2 -CF has a smaller Tafel slope in each sample, indicating that the reaction kinetics is promoted, such as Fig.14 shown.
[0076] In order to accurately reveal the composition of the syngas, the H 2 The ratio is compared to that of CO, which can be controlled by the applied potential. Fig.15 As shown, a reasonable proportion of Cu + / Cu 2+ Cu 3 Se 2 -CF helps to transfer H 2 / CO raw material ratio was adjusted from 0.8 to 6.0. Therefore, the Cu 3 Se 2 -CF H 2 The ratio of / CO is to match the synthesis gas composition for subsequent hydroformylation synthesis, which is formic acid, acetic acid and vinyl acetate, and can approach the ideal ratio of Fischer-Tropsch synthesis at -0.7 and -1.3V, such as Fig.16 As shown, the Fischer-Tropsch synthesis produces methanol and ethylene.
[0077] In addition to the syngas activity, the stability of the current and the H 2 The / CO ratio is crucial for the production of syngas. Fig.17 As shown, bulk electrolysis was performed continuously for 10 h, where the current density was kept constant and the Faradaic efficiency of syngas production was close to 100%. More importantly, H 2 The change in the CO / CO ratio is negligible, indicating the long-term durability of syngas production. 3 Se 2 The in situ synthesis strategy enables the catalyst to possess high performance for syngas production and great stability.
[0078] The present invention utilizes anion-regulated self-supporting Cu 3 Se 2 , H 2 O / CO2 Highly selective electrochemical conversion into high value-added / low-cost syngas. 0 The multidimensional composite structure of the boundary simultaneously regulates eCO 2 RR / HER, for optimizing CO 2 →The carbon conversion pathways of CO have incredible synergy.
[0079] The self-supporting copper selenide nanosheets regulate the adsorption strength of the key intermediates *COOH / *H and reduce the reaction energy barriers of *COOH formation and *CO desorption. The present invention shows that anion-regulated copper foam has broad prospects in the fields of high-energy and high-value-added fuels / chemicals and industrial / commercial syngas synthesis.
Claims
1. A method for preparing a self-supporting copper selenide nanosheet electrocatalyst, characterized in that: The following steps are involved: (1) immersing the copper foam in a mixed solution of alkali and persulfate, so that metal stripping and oxidation reactions occur in the solution to obtain self-supporting copper hydroxide nanobelts; (2) mixing and dissolving selenium powder and sodium borohydride powder to obtain a sodium hydrogen selenide precursor; the molar ratio of the selenium powder to the sodium borohydride is 4:1-5:1; (3) mixing a self-supporting copper hydroxide nanobelt with a sodium hydride selenide precursor and performing a hydrothermal reaction, the resulting product being the self-supporting copper selenide nanosheet electrocatalyst; in situ assembling copper selenide 2D nanosheets on a foam copper metal substrate having a 3D foam skeleton to obtain a multi-dimensional composite structure self-supporting copper selenide electrocatalyst; the fibers surrounded by the nanosheets in the self-supporting copper selenide nanosheet electrocatalyst have an internal pore structure; The temperature of the hydrothermal reaction is 175-185°C and the time is 12-14h.
2. The method for preparing the self-supporting copper selenide nanosheet electrocatalyst according to claim 1, characterized in that: In step (1), the molar ratio of the alkali to the persulfate is 19:1-20:
1.
3. The method for preparing the self-supporting copper selenide nanosheet electrocatalyst according to claim 1, characterized in that: In step (1), the thickness of the copper foam is 9-11 mm.
4. The method for preparing the self-supporting copper selenide nanosheet electrocatalyst according to claim 1, characterized in that: In step (1), the copper foam is pretreated with dilute hydrochloric acid and water.
5. The method for preparing the self-supporting copper selenide nanosheet electrocatalyst according to claim 1, characterized in that: In steps (1) and (2), the solvent used for dissolution is water.
6. Use of the self-supporting copper selenide nanosheet electrocatalyst prepared by the method according to claim 1 as a cathode catalyst for electrocatalytic carbon dioxide reduction under neutral conditions.
